Assessment of neurotoxic effects of methyl bromide in exposed workers - Acuña, M C; Díaz, V; Tapia, R; Cumsille, M A (Revista medíca de Chile, 1997)
Methyl bromide is an aliphatic hydrocarbon derivative used as a pesticide that causes skin, kidney, respiratory, liver and neurological damage. To assess the neurological and psychiatric damage caused by methyl bromide in exposed workers of seed and fruit export industries in a rural area near Santiago. We studied prospectively 15 male middle age workers before and after a fumigation period with methyl bromide, that lasted two to four weeks. According to the initial assessment, 5 of these subjects had a chronic exposure to the chemical. As controls, 10 non exposed workers matched for age, sex and working conditions were studied in two occasions. The evaluation included the WHO Neuro Behavior Core Test Battery, dynamometric and vibrator assessment of peripheral nerve function, the Nothingham test for psychological functioning and Titmus test for visual acuity. Methyl bromide levels were measured in blood and urine. Blood methyl bromide levels increased from 13.3 to 30 mg/dl after exposure. Symptoms that appeared with a higher frequency in exposed workers were insomnia, headache, paresthesiae, mood changes and loss of memory and concentration. In these subjects, the threshold for the Vibraton test increased from 2.4 to 2.85 sec, dynamometry showed a strength reduction in the right side from 51.4 to 47.2 kg and there was an increase in the score for negative auto-perception in the Nothingham test from 11.2 to 13.6. No deterioration in these tests were observed in unexposed workers. Acute and chronic methyl bromide exposure causes important psychological and neurological derangement.